2022
DOI: 10.26505/djm.23026680717
|View full text |Cite
|
Sign up to set email alerts
|

The role of anti-TPO as an additional analytical marker in thyroid disease patients in Erbil City

Abstract: Background: There is a connection among anti-TPO and anti-TG antibodies and levels of thyroid hormone and both alone or in grouping have been utilized to expect perfection of hypo or hyperthyroidism. Objective: Both alone or in grouping have been utilized to expect perfection of hypo or hyperthyroidism. Patients and Methods: This is a cross-sectional study achieved in the laboratories of Rizgary Teaching Hospital and Erbil Teaching Hospital in Erbil, Iraq, within the period of May 2020 to April 2021. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The demographical distribution of thyroid dysfunction patients and healthy people groups was done according to their age, gender, BMI, and family history in Table (1), the mean age of the patient group is 39.1 years, indicating the middle ages appear to be more susceptible to thyroid disorders. These results corroborated the results of other authors [12][13].…”
Section: Resultssupporting
confidence: 93%
“…The demographical distribution of thyroid dysfunction patients and healthy people groups was done according to their age, gender, BMI, and family history in Table (1), the mean age of the patient group is 39.1 years, indicating the middle ages appear to be more susceptible to thyroid disorders. These results corroborated the results of other authors [12][13].…”
Section: Resultssupporting
confidence: 93%
“…Globally, the current research findings corroborate international studies, including a notable demonstration that TPO-Ab levels were significantly elevated in both male and female patients diagnosed with hypothyroidism, in contrast to those with hyperthyroidism.]. Otherwise, the findings of the current study diverge from those of a research conducted in Erbil, Iraq, which revealed that the prevalence of TPO-Abs was greater in patients with hypothyroidism (63.6%) compared to those with hyperthyroidism [30].…”
Section: Abssupporting
confidence: 83%
“…As shown in Fig. 2, The findings of the current research indicate that the second age group (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) years are the most susceptible to infection with 37 patient (48.68%) with an age mean of (38.32). Middle-aged and older adults, especially females, exhibit a higher susceptibility to thyroid disorders.…”
Section: Absmentioning
confidence: 55%